Minding the Body : Psychotherapy in Cases of Chronic and Life-Threatening Illness. - Kaschak, Ellyn (Taylor and Francis, 2014)
Support and empower women who are coping with the pain, fear, and stigma of serious diseaseBeing diagnosed with cancer, chronic fatigue syndrome, or fibromyalgia is a traumatic event that takes place at a time when the patient is already feeling physically (and often emotionally) drained. Minding the Body combines feminist and social constructionist approaches to offer an intimate look into the ways a therapist can help clients cope with the pain, fear, and stigma of serious disease. Minding the Body offers an alternative to the reductive view of the mind-body connection and.